Pengaruh Branding “Colorful Medan” dan Event MICE Terhadap Minat Berkunjung Kembali Ke Kota Medan - Ginting, Juni Anggraini (Yayasan Literasi Sains Indonesia, 2022)
This study aims to explain the EFFECT OF “COLORFUL MEDAN” BRANDING AND MICE EVENTS ON INTEREST TO VISIT THE CITY OF MEDAN. This type of research uses explanatory research, and data is obtained from distributing questionnaires to 106 domestic tourists who travel to MICE events in Medan City. This study uses descriptive analysis and path analysis. The results showed that the Colorful Medan branding variable and the MICE event had a direct effect on the interest of tourists to visit again. Based on the results of the study, it is better for the Medan City Government and MICE industry players to work together in maintaining and socializing Medan's colorful branding by increasing the promotion of all types of objects and tourist attractions in Medan City. This research is limited to the variables of city branding, MICE events and intention to visit again. Hopefully, through this research, MICE branding and tourism in Medan City can be further developed to the fullest.Keywords: City Branding, MICE Event, Interest to Visit Again.